2021
DOI: 10.1007/s12325-020-01612-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Long-Acting GnRH Agonist Follicular Protocol with the GnRH Antagonist Protocol in Women Undergoing In Vitro Fertilization: A Systematic Review and Meta-analysis

Abstract: Introduction: To evaluate the effectiveness and safety of long-acting GnRH agonist follicular and GnRH antagonist protocols among women undergoing in vitro fertilization (IVF) using data published in both English-language and Chinese studies. Methods: We systematically searched the PubMed, Embase, Cochrane, CNKI, and Wanfang databases up to March 2019 for studies comparing long-acting GnRH agonist follicular and GnRH antagonist protocols in women undergoing IVF. The primary outcome was live

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…Treatment with a GnRH antagonist is a routine ovulation stimulation protocol and has been used to prevent premature LH surge since the 1990s (8,9). There are a large number of randomized controlled, prospective and retrospective studies on GnRH antagonist regimens that fully prove the effectiveness and safety of these regimens (10)(11)(12)(13). Regarding the PPOS protocols, although it has not been applied for a long time, studies have shown that it can achieve exact effectiveness and safety in different populations (19)(20)(21)(22).…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with a GnRH antagonist is a routine ovulation stimulation protocol and has been used to prevent premature LH surge since the 1990s (8,9). There are a large number of randomized controlled, prospective and retrospective studies on GnRH antagonist regimens that fully prove the effectiveness and safety of these regimens (10)(11)(12)(13). Regarding the PPOS protocols, although it has not been applied for a long time, studies have shown that it can achieve exact effectiveness and safety in different populations (19)(20)(21)(22).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Gonadotropin-releasing hormone (GnRH) antagonist is the routine ovulation stimulation protocol ( 8 , 9 ). There are a large number of randomized controlled, prospective and retrospective studies on GnRH antagonist regimens that fully prove the effectiveness and safety of GnRH antagonist regimens ( 10 13 ). However, it has been reported that GnRH antagonist protocols have a 0.34% to 8.0% chance of failing to control the LH surge, and increased age and diminished ovarian reserve are the main risk factors ( 14 – 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recently review combined and analysed seven studies, including proportions of normal ovarian responders, polycystic ovary syndrome (PCOS), and poor responders. Despite increased risk of ovarian hyperstimulation syndrome (OHSS), the long-acting GnRH agonist follicular protocol was still beneficial in improving live birth rate than GnRH antagonist protocol (25).…”
Section: A B Cmentioning
confidence: 99%
“…The GnRH agonist and GnRH-ant protocols are well-established methods for controlled ovarian hyperstimulation among patients who are receiving assisted reproductive technology (ART) [11]. The GnRH-a protocol was developed in the 1980s and is used to prevent premature LH outpouring, thereby increasing the number of retrieved oocytes and pregnancy rates.…”
Section: Introductionmentioning
confidence: 99%
“…The GnRH-ant protocol was introduced in the 1990s; it can competitively block GnRH receptors and cause a rapid suppression of Gn release. The GnRH-ant protocol results in a lower risk of severe ovarian hyperstimulation syndrome (OHSS) and is more convenient for patients because of the shorter duration of Gn administration and lower Gn dose [11,12]. Current reports are not consistent in comparing the clinical outcomes of the GnRH-a and GnRH-ant protocols.…”
Section: Introductionmentioning
confidence: 99%